1998
DOI: 10.1037/0012-1649.34.2.299
|View full text |Cite
|
Sign up to set email alerts
|

Does low self-regard invite victimization?

Abstract: Two hypotheses were tested. The first was that low self-regard contributes over time to victimization by peers. The second was that behavioral vulnerabilities (e.g., physical weakness, manifest anxiety, poor social skills) are more likely to lead to victimization over time when children have low self-regard than when they are "self-protected" by healthy self-regard. Participants were 189 third-through 7th-grade boys and girls; data were collected in the fall and the spring of the school year. Both hypotheses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
359
3
16

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(404 citation statements)
references
References 30 publications
26
359
3
16
Order By: Relevance
“…These findings indicate that victimized children are more likely to engage in submissive, withdrawn, or aggressive social behaviors which perpetuate the cycle of victimization (Boivin, Hymel, & Bukowski, 1995) while children engaged in positive, prosocial behaviors are at a lower risk for peer victimization (Egan & Perry, 1998;Schwartz, Dodge, & Coie, 1993). Yet current research findings suggest there is more heterogeneity in the profiles of victimized children than prior research has suggested, and that these differences may lead to varied adjustment outcomes for victimized children.…”
Section: Prosocial Behavior As a Protective Factormentioning
confidence: 91%
“…These findings indicate that victimized children are more likely to engage in submissive, withdrawn, or aggressive social behaviors which perpetuate the cycle of victimization (Boivin, Hymel, & Bukowski, 1995) while children engaged in positive, prosocial behaviors are at a lower risk for peer victimization (Egan & Perry, 1998;Schwartz, Dodge, & Coie, 1993). Yet current research findings suggest there is more heterogeneity in the profiles of victimized children than prior research has suggested, and that these differences may lead to varied adjustment outcomes for victimized children.…”
Section: Prosocial Behavior As a Protective Factormentioning
confidence: 91%
“…Victims are more likely to suffer from long-lasting social isolation, loneliness, anxiety and poor social competence (Egan and Perry 1998;Forero et al 1999;Veenstra et al 2005;KochenderferLadd and Wardrop 2001), and to have an increased risk of self-harm, suicidal ideation, attempting and completing suicides (Barker et al 2008;Klomek et al 2009;Winsper et al 2012). They are also more prone to developing symptoms of psychosis, such as auditory hallucinations and paranoid ideation (Lataster et al 2006;Schreier et al 2009).…”
mentioning
confidence: 99%
“…When victimization does occur, a "vicious cycle" may be set in motion, in which repeated victimization amplifies behavioral and psychological features that invite further victimization (Hodges & Perry, 1999). Among elementary school children, interpersonal (e.g., peer rejection, poor social skills) and intrapersonal (e.g., internalizing distress, low selfregard) factors predicted increases in victimization over the course of a year, and victimization predicted increases in psychosocial maladjustment (Egan & Perry, 1998;Hodges and Perry, 1999). This reciprocal pattern also holds in early adolescence.…”
mentioning
confidence: 99%